Fabrication and Characterization of Metal and Metal Oxide Nanostructures Grown by Metal Displacement Deposition Into Anodic Alumina Membranes - R. Inguanta; G. Ferrara; S. Piazza; C. Sunseri (Chemical Engineering Transactions, 2011)
Abstract preview not available - see full-text PDF article.